ChemInform Abstract: A Novel Green Synthesis of α/β‐Amino Acid Functionalized Pyrimidinone Peptidomimetics Using Triazole Ligation Through Click‐Multi‐Component Reactions. Issue 22 (3rd June 2014) - Balan, Biny; Bahulayan, D.
Abstract Dihydropyrimidinone precursors undergo 1, 3‐dipolar cycloaddition with small peptide like azides, generated from Ugi or alternate Mannich type multicomponent reactions.